Effect of Covid pandemic on immunization status of children in tertiary care Hospital of North India: reason for partial and non-immunization a cross-sectional study - Narender Kumar; Pinki Allyhan; Anju Aggarwal (BMC, 2024)
Abstract Background Low immunization coverage in India attributes to many factors including sociodemographic factors and people's behavior. COVID-19 pandemic resulted in disruptions in achieving optimum availability and utilization of immunization services. This study was carried out to find out the immunization status of children in the post COVID era and various factors responsible for non-immunization during the pandemic. Methods This cross-sectional study included parents of 225 admitted children aged 1-6 years were interviewed using a semi-structured open-ended questionnaire. Children were classified as completely immunized, partially immunized and unimmunized on the basis of vaccines missed given under first year of life. Reasons for non-immunization and delay/missed vaccination during COVID-19 pandemic were recorded. Results Of the 225 children, 162 (72%; 95% CI 66-78%) were completely immunized, 55 (24.4%; 95% CI 19-30%) were partially immunized and 8 (3.6%; 95% CI 1-6%) were unimmunized. Parents with hospital deliveries, higher education level and lesser birth order were more likely to have children with better immunization status (p < 0.05). First dose of measles scheduled at 9 months and 3rd dose of pentavalent vaccine/OPV/Rotavirus vaccine scheduled at 14 weeks were most commonly missed vaccines among partially immunized. Lack of awareness (n = 36, 57.1%; 95% CI 45-70%) was the common reason for partial and non-immunization followed by illness of child (n = 21, 33.3%; 95% CI 21-45%) and COVID-19 pandemic (n = 11, 17.4%; 95% CI 8-27%). Pandemic was reason for delay in 50 (22.2%; 95% CI 17-28%) children. Restrictions of movement (64%; 95% CI 50-78%), fear of being exposed to COVID-19 (52%; 95% CI 38-66%) were the most common reasons for delay during the pandemic. Of the 50 children who had delay due to pandemic, 39 children (17.3%; 95% CI 12-22%) received their catch-up immunization after the pandemic. No child remained completely unimmunized due to COVID-19 pandemic. Conclusions Although COVID-19 pandemic resulted in disruptions in routine immunization services, sociodemographic factors such as awareness for immunization, parental education and various beliefs for immunization were responsible for the children remaining unimmunized or partially immunized after the pandemic.